TRAINING ON POLITICAL 'HOAX' INFORMATION LITERACY FOR THE INDONESIAN COMMUNITY ORGANIZATION (PERMAI) PENANG ISLAND - MALAYSIA - Budianto, Heri (Program Studi Ilmu Komunikasi Universitas Pamulang, 2026)
The entire spectrum of the nation's colors is a media target that is carefully considered. News programs or political information are presented to audiences of all ages, including the youth. The fact is that news programs and political information also target the youth as an undeniable market. Furthermore, the youth serve as educators for their children. A competent successor generation is needed in various fields, and this also requires the role of parents, especially the youth. The issue of the ability to use media is also one of the crucial aspects in the media literacy education process. To ensure this, it is not enough to only disseminate information but also to actively and continuously ensure the implementation of media literacy education to enhance the activities of citizens, both individually and collectively. The title of this community service is Information Literacy Training on Political